Peranan Analisis Biaya Kualitas Dalam Meningkatkan Efisiensi Biaya Produksi - Angelia, Angelia; Wahyuningsih, Diah; Herawati, Heti (Institut Bisnis dan Informatika Kesatuan, 2019)
Apparently there are some brands pay less attention and take for granted to the quality of their products. In addition to increasing sales, quality attracts consumers and provides benefits for the company. Nonetheless, most MSMEs fail in running their businesses, one of which is due to the inability to analyze the cost of quality and production efficiency. This research aims to analyze (1) components and calculation of production costs on MSMEs sandals Nagaya, (2) components and calculation of quality costs at the company in MSMEs sandals Nagaya, (3) The relationship between quality costs with production costs in increasing production costs. The results show that calculation of the cost of production is carried out very differently than common method suggested. The cost of production of MSMEs Nagaya is calculated by adding direct material costs, direct labor costs, factory overhead costs. There is no depreciation of the machine or building because MSMEs' workforce has its own machines and the factory sites joins with the owner's house. There are quality cost such as preventive cost, and internal failure cost. There’s no external failure costs because the owner does not implement both warranty system and customer complaints handling system, and there is no decrease in turnover. Cost of quality was determined at 1% of total production costs. This shows that the cost of quality has no significant influence on the production activities of MSMEs Nagaya.